Structure, biomass and carbon assessment of chronosequence rehabilitated tropical forest stands - Kueh, Roland Jui Heng (2013)
Global forest area loss and degradation are some of the major global environmental issues. These issues have elevated the role of the remaining secondary and rehabilitated forests in providing goods and services to mankind. The secondary and rehabilitated forests have the potential to assimilate and store relatively large amount of biomass and carbon. Such information is rather limited in rehabilitated forest especially for tropical region. The objectives of this study were to: (i) determine biomass distribution of a rehabilitated forest, (ii) develop allometric biomass equation, and (iii) estimate carbon fixed in the trees and soil of a rehabilitated forest. The study site was at the UPM-Mitsubishi Corporation Forest Rehabilitation Project, UPM Bintulu Sarawak Campus, Bintulu, Sarawak. The research was conducted in 2009. Plot of 20 x 20 m was established each at 19-(Plot 1991), 10-(Plot 1999), one-year-old (Plot 2008) rehabilitated forests and ± 23-year-old natural regenerating secondary forest (Plot NF). Modified allometric equations were used to estimate the biomass and carbon distribution and storage. Analyses showed that the contribution of tree component biomass/carbon to total biomass/carbon was in the order of main stem > branch > leaf. The total above ground biomass for the rehabilitated forest ranged from 0.1- 118.9 t/ha compared to natural regenerating secondary forest of 134.2 t/ha while the total above ground carbon was 0.1–54.0 t/ha and 61.0 t/ha, respectively. The above ground storage (above ground biomass and standing crop litter) was about 70-72% of the total biomass and 64-67% of total carbon in 19-year-old rehabilitated and natural regenerating secondary forests, while 10- and one-year-old rehabilitated forests were 42% and 10% of the total biomass, 36% and 8% of the total carbon, respectively. The below ground storage was about 28-30% of the total organic matter and 33-36% of the total carbon in 19-year-old rehabilitated and natural regenerating secondary forests, while for 10- and one-year-old rehabilitated forests were 58% and 90%, 64% and 92%, respectively. The above ground forest restored the soil organic matter and soil carbon in the rehabilitated forest and this provides organic matter inputs in the form of above and below ground litter. The variations of the biomass and carbon storage were contributed by the differences in the forest structure, microclimatological and soil conditions. These indicate the different successional stages at the study plots.Forest structural analysis showed that the rehabilitated forest performs better in terms of structural characteristics compared to the adjacent natural regenerating secondary forest. However, the rehabilitated forest exhibited climax species community despite having lower species diversity. Microclimatological analyses showed that the microclimatological conditions inside the forests were less extreme and more humid compared to the open space. In addition, soil analyses showed that the acidic soils in all the study sites were low in nutrients and infertile. The stressful environment created through high density tree planting has promoted accelerated performance of the physical tree characteristics. This has contributed to the higher biomass and carbon storage. Older rehabilitated forest of 19 years old had total above ground biomass and carbon storage comparable to the natural regeneration secondary forest. This reaffirms the need for human intervention in rehabilitating degraded forest areas through tree planting initiatives. It can be concluded that forest rehabilitation programme showed potential in facilitating the recovery of biomass and carbon storage.